The Eksistensi Yayasan Widya Ganesha Kadiri dalam Pembinaan Pasraman-Pasraman di Kabupaten Kediri Jawa Timur: Eksistensi Yayasan Widya Ganesha Kadiri dalam Pembinaan Pasraman-Pasraman di Kabupaten Kediri Jawa Timur - Candra, Widya Ayu; Kusuma, I Made Wirahadi; Putra, I Gede Garbha (UHN IGB Sugriwa Denpasar, 2024)
Religious education is a pillar in improving the quality of religious knowledge. In Hinduism, Religious Education functions to increase sradha and brahmacari bhakti to Ida Sang Hyang Widhi. Hindu Religious Education Institutions in formal and non-formal channels are pasraman. Kediri Regency is one of the regencies in East Java Province which has 13 non-formal boarding schools. Based on a decree issued by Parisada Hindu Dharma Indonesia (PHDI) Kediri Regency, the Pasramans are under the auspices of a foundation called the Widya Ganesha Kadiri Foundation. Before the pasraman came under the auspices of the foundation, the pasraman had experienced a vacuum caused by a lack of orderly management, a lack of teaching staff, inconsistencies in the presence of brahmacari, a lack of facilities and infrastructure, and the Covid-19 pandemic. After the pasraman was sheltered by the foundation, stretching activities for the revival of the pasraman began. The foundation seeks to help revive the pasramans through coaching. This study aims to find out what forms of coaching are carried out by foundations, what are the obstacles and efforts in implementing coaching, as well as the impact of coaching carried out by foundations. The theory used in this research is Structural Functional Theory, Constructivism Theory, and Motivation Theory. The results of the research show that the form of foundation coaching for pasramans is realized through the implementation of work programs. There are seven types of foundation work programs, five of which have been implemented, while the other two are still in the process of being implemented. There were obstacles in the implementation of work programs which resulted in several work programs not being implemented. The foundation is currently trying to overcome these obstacles so that the work program can be fully implemented. But even so, the existence of the foundation in fostering pasramans was able to have a positive impact on the generation of pasramans in Kediri Regency, East Java.